How to draw flowers and trees in simple steps - Whittle, Janet; Brown, Penny; John-Naylor, Denis (London Search Press, 2012)
A simple guide on drawing flowers and trees
Arts (Drawing)
1 13
Keywords: Drawing -- Technique -- Juvenile literature; Flowers in art -- Juvenile literature; Trees in art -- Juvenile literature; Drawing; Flowers in art; Trees in art